1981
DOI: 10.1203/00006450-198107000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Urine Calcitonin in Normal Children

Abstract: SummaryAlthough it is known that calcitonin decreases bone resorption, lowers serum calcium and phosphate, and influences the urinary excretion of these ions, its effect upon skeletal maturation in growing children has not been elucidated. Conceivably, the higher serum calcitonin levels that have been reported in children may promote bone formation and growth.To study immunoreactive urine calcitonin (iCT) in normal children, we used the radioimmunoassay (RIA) which we had developed previously to measure the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
3
0
0
Order By: Relevance
“…We found that CT levels decreased with advancing Tanner stages. Silva et al [44] could support our findings by detecting a decrease of CT during puberty in a study of the early 1980s.…”
Section: Discussionsupporting
confidence: 85%
“…We found that CT levels decreased with advancing Tanner stages. Silva et al [44] could support our findings by detecting a decrease of CT during puberty in a study of the early 1980s.…”
Section: Discussionsupporting
confidence: 85%
“…These findings led us to investigate uCTi levels in males and females of different ages. Silva et al (1980) reported previously that levels of uCTi fall progressively with age in children, observations which are compatible to those reported in this report. Females aged 11-15 years, whose pubertal growth spurt was completed earlier than males, had significantly lower uCTi levels than males of the same age; similar observations were found in females 7-12 years of age in the study of Silva et al (1980).…”
Section: Methodssupporting
confidence: 82%
“…Silva et al (1980) reported previously that levels of uCTi fall progressively with age in children, observations which are compatible to those reported in this report. Females aged 11-15 years, whose pubertal growth spurt was completed earlier than males, had significantly lower uCTi levels than males of the same age; similar observations were found in females 7-12 years of age in the study of Silva et al (1980). Although there is general agreement that circulating CT levels are high in children when compard to adults, controversy exists between previous reports and our observation with regard to the uCTi in elderly subjects.…”
Section: Methodssupporting
confidence: 82%